Information Provision and Search Frictions: Evidence from the Taxi Industry in Singapore - Agarwal, Sumit; Cheng, Shih-fen; Keppo, Jussi; Wang, Long; Yang, Yang (The Review of Economics and Statistics, 2025)
Search frictions and misallocation are common in decentralized transportation markets. Using novel trip-level data of taxis in Singapore, this paper examines the impactof real-time demand information at airport terminals on search frictions. The in-formation reduces taxi supply misallocation, increasing deadheading speed by 16.3%and decreasing deadheading time by 10.77%, benefiting both passengers and drivers.It raises daily earnings by $3.70 USD and adds 6.2 minutes of operational time perairport-trip taxi. Spatial spillovers are primarily observed among drivers in adjacentdistricts. Taxis from the Budget Terminal and drivers with fewer prior airport pickups benefit more from this information.